Career Guidance Services to Form a Career Identity for Vocational High School Students - Abdul Karim; Nurus Sa'adah (Bisma The Journal of Counseling, 2021)
Constraints and obstacles experienced by Vocational High School (SMK) students in the academic field are not only about the lack of information about the world of work or higher education, but the ability of SMK students in preparing their careers is still relatively low, students do not yet have a clear picture of their abilities, interests, and abilities. their goal. The purpose this a research is to form the career identity of students through career guidance services. This study uses descriptive qualitative research methods through Counseling Guidance Actions (PTBK). Data analysis was obtained from observations, interviews, and documentation. Based on the results of interviews and observations in this study, there is a significant difference between before and after being given career guidance actions to form career identities for class XII students of SMK Darussalam Blokagung Tegalsari Banyuwangi. Thus, students have a change in career identity after being given career guidance services, so it can be concluded that career guidance services can be used to form an identity in students' careers.